Identifying gravity waves launched by the Hunga Tonga-Hunga Ha‘apai volcanic eruption in mesosphere/lower thermosphere winds derived from CONDOR and the Nordic Meteor Radar Cluster - Stober, Gunter; Liu, Alan; Kozlovsky, Alexander; Qiao, Zishun; Krochin, Witali; Shi, Guochun; Kero, Johan; Tsutsumi, Masaki; Gulbrandsen, Njål; Nozawa, Satonori; Lester, Mark; Baumgarten, Kathrin; et al. (Copernicus Publications, 2022)
The Hunga Tonga-Hunga Ha‘apai volcano eruption was a unique event that caused many atmospheric phenomena around the globe. In this study, we investigate the atmospheric gravity waves in the mesosphere/lower thermosphere (MLT) launched by the volcanic explosion in the Pacific leveraging multistatic meteor radar observations from the Chilean Observation Network De Meteor Radars (CONDOR) and the Nordic Meteor Radar Cluster in Fennoscandia. MLT winds are computed using a recently developed 3DVAR+DIV algorithm. We found an eastward and a westward traveling gravity wave in the CONDOR zonal and meridional wind measurements, which arrived 12 hours and 48 hours after the eruption, and one in Nordic Meteor Radar Cluster that arrived 27.5 hours after the volcanic detonation. We obtained observed phase speeds for the eastward great circle path at both locations of about 250 m/s and 170–150 m/s for the opposite propagation direction. The intrinsic phase speed was estimated to be 200–212 m/s. Furthermore, we identified a potential lamb wave signature in the MLT winds using 5 minute resolved 3DVAR+DIV retrievals.